Solid Financing of the EU - Kube, Hanno; Reimer, Ekkehart (Lehmanns Media, 2021)
The system of EU Own Resources undergoes disruptive changes. The EU finalized a new Multiannual Financial Framework, decided on huge extra spending under the paramount Next Generation EU program and took loans. These changes have been accompanied by large-scale ECB and ESCB programs. While some observers prefer a more traditional, thus more reluctant financial framework, others dream of a Hamiltonian moment or debate about the introduction of a genuine European tax. Next to political and economic uncertainties, each of these steps triggers intricate legal questions.These questions are analyzed in this book. Thorough papers by Martin Nettesheim and Edoardo Traversa as well as further clear-cut statements by prominent experts contribute to a lively debate on the financial future of Europe.